Eleven-year summary of KSU on-farm swine testing program - Nichols, David A.; Pollmann, D.S.; Olson, W.G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Records of approximately 11,000 boars and 6,000 gilts enrolled in the KSU on-farm swine test program were summarized. Both boars and gilts reached 220 lbs 5 days sooner in 1980 than 1970. Of the traits evaluated, the largest improvement was a reduction in backfat thickness of 25% from 1970 to 1980. Loin-eye area increased from 1970 to 1975 but declined from 1975 to 1980.
Keywords: Swine; KSU On-Farm Swine Testing Program